2012
DOI: 10.1155/2012/128694
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Skin-Mediated Detoxification Contributes to Oxidative Stress and Insulin Resistance

Abstract: The skin, the body's largest organ, plays an important role in the biotransformation/detoxification and elimination of xenobiotics and endogenous toxic substances, but its role in oxidative stress and insulin resistance is unclear. We investigated the relationship between skin detoxification and oxidative stress/insulin resistance by examining burn-induced changes in nicotinamide degradation. Rats were divided into four groups: sham-operated, sham-nicotinamide, burn, and burn-nicotinamide. Rats received an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…sweat glands [66][67][68][69]. Skin barrier retards excretion of accumulated toxins, while skin injury disturbs skin excretory functions [70] with retention of drugs and endogenous metabolites [71][72][73]. Based on that, cupping therapy is so beneficial as it opens skin barrier and enhances skin excretory role.…”
Section: A-before Application Of Wet Cupping Therapymentioning
confidence: 99%
“…sweat glands [66][67][68][69]. Skin barrier retards excretion of accumulated toxins, while skin injury disturbs skin excretory functions [70] with retention of drugs and endogenous metabolites [71][72][73]. Based on that, cupping therapy is so beneficial as it opens skin barrier and enhances skin excretory role.…”
Section: A-before Application Of Wet Cupping Therapymentioning
confidence: 99%
“…Moreover, sweat glands of human skin (eccrine sweat glands) measure about the weight of one kidney (about 100 g) and can excrete numerous drugs, metals, xenobiotics [65][66][67], endogenous chemical and biological substances e.g. neurotransmitters, cytokines, heavy metals and sterols [68,[74][75][76]. Therefore, it can be concluded that decreased skin functions due to burn injuries may increase the Taibah theory for 2 nd part of Al-hijamah (WCT) risk of accumulation of toxic substances in the body.…”
Section: Al-hijamah Enhances Excretory Skin Functions and Clears Interstitial Spacesmentioning
confidence: 99%
“…complicated burns occur in full-thickness skin as evidenced by the report by Liu et al who reported that the expression of enzymes metabolizing xenobiotics, drugs and ROS scavenging enzymes was not detected in the full-thickness burnt rat skin. Burn causes increased generation of free radicals as hydrogen peroxide [76]. Based on that, WCT opens skin barrier and may cause relief of that harmful stress.…”
Section: Al-hijamah Enhances Excretory Skin Functions and Clears Interstitial Spacesmentioning
confidence: 99%
“…Diurnal temperature range (DTR), Mean temperature (T mean) and relative Humidity (RH) are important indicators to assess the state of meteorological change (Yang et al 2018). A review on temperature and metabolic syndrome suggests that low ambient temperature may be an important risk factor for metabolic syndrome (Liu et al 2012). Another review from Mississippi shows an association between heat exposure and the prevalence of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%